Effects of dietary calorie restriction or exercise on the PI3K and Ras signaling pathways in the skin of mice - Xie, Linglin; Jiang, Yu; Ouyang, Ping; Chen, Jie; Doan, Hieu; Herndon, Betty; Sylvester, Jessica E.; Zhang, Ke; Molteni, Agostino; Reichle, Marie; Zhang, Rongqing; Haub, Mark D.; et al. (My University, 2008)
Weight control by exercise and dietary calorie restriction (DCR) has been associated with reduced cancer risk, but the underlying mechanisms are not well understood. This study was designed to compare the effects of weight loss by increasing physical activity or decreasing calorie intake on tumor promoter-induced Ras-MAPK and PI3K-Akt pathways. SENCAR mice were randomly assigned to one of the following five groups: ad libitum-fed sedentary control, ad libitum-fed exercise (AL+Exe), exercise but pair-fed at the amount as controls (PF+Exe), 20% DCR, and 20% DCR plus exercise (DCR+Exe). After 10 weeks, body weight and body fat significantly decreased in the groups of DCR, DCR+Exe, and PF+Exe when compared with the controls. AL+Exe did not induce weight loss due to, at least in part, increased food intake. Plasma IGF-1 levels reduced significantly in DCR and DCR+Exe but not PF+Exe. The protein H-Ras and activated Ras-GTP significantly decreased in TPA-induced skin tissues of DCR-fed mice but not exercised mice. PI3K protein, phosphoserine Akt, and p42/p44-MAPK were reduced, however, in both DCR and PF+Exe groups. Immunohistochemistry demonstrated that the significantly reduced H-Ras occurred in subcutaneous fat cells, while the reduced PI3K and PCNA took place only in the epidermis. Plasma leptin decreased in PF+Exe, DCR, and DCR+Exe, while the caspase-3 activity increased in DCR+Exe only. Genomic microarray analysis further indicated that the expression of 34 genes relevant to PI3K and 31 genes to the MAPK pathway were significantly regulated by either DCR or PF+Exe treatments. The reduced PI3K in PF+Exe mice was partially reversed by IGF-1 treatment. The overall results of this study demonstrated that DCR abrogated both Ras and PI3K signaling, which might inhibit TPA-induced proliferation and anti-apoptosis. Selective inhibition of PI3K by PF+Exe but not AL+Exe seems more attributable to the magnitude of the caloric deficit and/or body fat loss than diet versus exercise comparison.
Keywords: Dietary calorie restriction; Exercise; Cancer prevention; Signal pathway; Mice